Laboratory Test Indirectly Reveals the Unreliability of RNA-Dependent 16S rRNA Amplicon Sequences in Detecting the Gut Bacterial Diversity of Delia antiqua - Miaomiao Li; Xin Cao; Linfeng Xu; Luyao Lin; Xiaoqing Wu; Susu Fan; Xinjian Zhang; Fangyuan Zhou (Insects, 2025)
In insect–microbe symbiosis, understanding the diversity of associated bacteria is crucial. DNA-dependent sequence methods are widely used to assess microbial diversity in insects, but they cannot distinguish between live and dead microbes. In contrast, RNA-dependent sequencing can identify alive bacterial communities, making them more suitable for evaluating alive microbiota diversity. However, its practical reliability in insect–microbe symbiosis remains poorly validated. This study investigated larval gut bacteria diversity of Delia antiqua, a major pest of Liliaceae crops, by employing both DNA- and RNA-dependent 16S rRNA amplicon sequencing. The reliability of both sequencing methods was evaluated by comparing the effects of synthetic communities (SynComs, constructed according to DNA- or RNA-dependent sequencing) and bacterial communities from wild larvae on axenic larvae. Results revealed significant differences in bacterial community between DNA- and RNA-dependent sequence samples. Compared to bacterial communities from wild larvae, the SynCom constructed based on RNA-dependent sequencing exhibited inhibition effects on D. antiqua larvae survival and body weight, while DNA-dependent SynCom did not, suggesting that DNA-dependent methods were superior for assessing symbiotic microbiota in D. antiqua. This work will provide insights into microbial diversity detection in D. antiqua and offer a framework for other insect–microbe studies.